2021
DOI: 10.1111/ppl.13445
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, physiological and biochemical changes in Magnolia zenii Cheng seed during development

Abstract: An understanding of the seed dynamics of endangered plant species, such as Magnolia zenii Cheng, is important for successful conservation. This study examined the morphological, physiological and biochemical changes that occur in M. zenii Cheng during seed development to determine the appropriate harvest stage. The appearance of the seeds was influenced by the physiological and biochemical changes occurring during the developmental period, during which the colour of the fruits changed from green to red, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Among them, FUM, MDH, and ODGH may be targeted for TCA pathway regulation [ 46 ]. Furthermore, the PPP is a supplemental source of energy metabolism that directly oxidizes sugar and complements glycolysis to provide cells with NADPH and material to sustain seed germination, as well as providing pentose phosphate for nucleotide metabolism [ 47 ], the expression of its key genes was also down-regulated ( Table S1 ). Taken together, it appears that the entire energy supply chain in safflower seeds is severely damaged during the aging process and increasingly fails to provide sufficient energy for seed germination and seedling establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, FUM, MDH, and ODGH may be targeted for TCA pathway regulation [ 46 ]. Furthermore, the PPP is a supplemental source of energy metabolism that directly oxidizes sugar and complements glycolysis to provide cells with NADPH and material to sustain seed germination, as well as providing pentose phosphate for nucleotide metabolism [ 47 ], the expression of its key genes was also down-regulated ( Table S1 ). Taken together, it appears that the entire energy supply chain in safflower seeds is severely damaged during the aging process and increasingly fails to provide sufficient energy for seed germination and seedling establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Condensed tannins, a group of flavonoids were observed to increase throughout seed development in common bean and decreased after seed maturation [69]. A study in Magnolia zenii Cheng revealed a significant increase in soluble sugar, protein and lipid content of seed between 30 to 165 DAF [70]. In capsicum baccatum, [51] observed that soluble protein content increased by 66% from 10 to 40 DAA and remained unchanged until last harvest at 80DAA while neutral lipids content increased 14-fold between 10 and 30 DAA, reduced from 30 to 60 DAA and later increased until 80 DAA.…”
Section: Changes In Biochemical Seed Quality During Seed Development ...mentioning
confidence: 99%
“…The pentose phosphate pathway is a supplementary source of cellular energy that can directly oxidize sugars and complement glycolysis to provide the cell with NADPH and materials to promote seed germination (Wang et al, 2021). During the development of Arabidopsis, G6P is metabolized to erythrose 4phosphate, ribulose 5-phosphate, and sedoheptulose 7-phosphate with the release of NADPH and ATP through the pentose phosphate pathway to promote plant development (Andriotis and Smith, 2019).…”
Section: Pentose Phosphate Pathway Is Activated During Z Marina Seed ...mentioning
confidence: 99%